Investigating the anti-inflammatory activity of an ethanolic extract from Artocarpus tonkinensis leaves using a collagen antibody-induced arthritic mouse model - Quan, Tran Duc; Dao Duc Thien,; Tam, Nguyen Thanh; Hoang Anh, Nguyen Thi; Cuc, Nguyen Thi; Nga, Nguyen Thi; Sung, Tran Van; Hong Nhung, Le Thi; Sa, Nguyen Hoang; Adorisio, Sabrina; Delfino, Domenico V.; Thao, Do Thi; et al. (Vietnam Journal of Science and Technology, 2018)
The obtained results here demonstrate that the 70% ethanolic leaf extract of A. tonkinensis (AT2), traditionally used in Vietnamese folk medicine for treating arthritic symtoms, has beneficial effects on pro-inflammatory cytokine inhibition and in an experimental arthritic mouse model. LPS-stimulated RAW 264.7 macrophages treated with AT2 showed a significant decrease in the production of IL-6 and TNFa at concentrations of 12.5, 25 and 50 µg/mL (P<0.05), indicating its potential anti-inflammatory properties. Treatment of CAIA mice with AT2 also led to diminish the incidence of arthritis at doses of 200 and 300 mg/kg body weight.